2017
DOI: 10.24083/apjhm.v12i3.53
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Competence of Evidence-Informed Decision-Making Amongst Health Service Managers

Abstract: Objective: Evidence-informed decision-making (EIDM) amongst health service managers has been positively linked to better decision outcome, hence more effective healthcare provision. Efforts to improve EIDM practice are required to meet the current challenging healthcare environment. One key step to improve such practices is skill enhancement. The purpose of the study is the measure the competence of mid-level managers in two Victorian hospitals in applying EIDM in their roles. Design: The competence of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Likewise, some of the primary healthcare managers in Timor-Leste were revealed not to be competent in problemsolving on financial management in their jobs (Lopes et al, 2019). The low score in critically appraising the validity and relevance of evidence competency could be attributed to the low use of evidence in making managerial decisions in healthcare (Liang, Howard, & Wollersheim, 2017). This could be caused by the actual limited use of the available evidence to pp.…”
Section: Evidence-informed Decision Makingmentioning
confidence: 99%
“…Likewise, some of the primary healthcare managers in Timor-Leste were revealed not to be competent in problemsolving on financial management in their jobs (Lopes et al, 2019). The low score in critically appraising the validity and relevance of evidence competency could be attributed to the low use of evidence in making managerial decisions in healthcare (Liang, Howard, & Wollersheim, 2017). This could be caused by the actual limited use of the available evidence to pp.…”
Section: Evidence-informed Decision Makingmentioning
confidence: 99%
“…Other research specifically explored the competencies of evidence-driven healthcare managers. Liang, Howard and Wollersheim (2017) translated the competency of evidence-informed decisionmaking into behavioural descriptors, which were primarily process-oriented and did not refer to personal characteristics. Wright et al (2016), in contrast, focused on understanding the characteristics of evidence-driven managers through a case study where a manager approached an operational hospital problem in an evidence-based manner.…”
Section: Ebmgt In the Healthcare Contextmentioning
confidence: 99%
“…For example, among the five competency domains identified by the Healthcare Leadership Alliance (HLA), two domains -'knowledge of the healthcare environment' and 'business skills & knowledge' -included references to EBMgt, specifically to using research findings to establish practice models and teaching others to use research (Stefl and Bontempo, 2008). Similarly, Liang and colleagues (Liang, Howard and Wollersheim, 2017;Liang et al, 2013) identified evidence-informed decision-making as one of the core competencies for managers working in hospital settings. Moreover, McCarthy and Fitzpatrick (2009) identified promoting evidencebased decision-making, though referring mainly to clinical practice, as one of the competencies for nurse managers.…”
Section: Ebmgt In the Healthcare Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is limited empirical evidence on the performance of private hospitals in Nepal, especially as related to management. 1 This is despite the fact that evidence-based decision making is important for the efficient delivery of health care (Liang et al, 2017). We address this gap by examining the relationship between management and performance using Grande International Hospital (GIH) as a case study.…”
Section: Introductionmentioning
confidence: 99%